Visualizable vs. standard, non-visualizable steerable sheath for pulmonary vein isolation procedures: randomized, single-center trial. (19th May 2022) - Janosi, K; Debreceni, D; Janosa, B; Simor, T; Kupo, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Steerable sheaths are frequently used to improve catheter contact during pulmonary vein isolation (PVI) procedures. A new type of visualized (by electroanatomical mapping system) steerable sheath has become available in clinical treatment. Purpose: We aimed to compare procedural data of visualizable vs. non-visualizable steerable sheath assisted PVI procedures of patients with atrial fibrillation (AF). Methods: In this single-center randomized study, we enrolled a total of 58 consecutive patients who underwent PVI due to AF. In 30 patients, the procedures were performed using non-visualizable steerable sheath (Group 1), while we used visualizable steerable sheath for PVI in 28 cases (Group 2). Results: Compared to Group 1, using the visualizable sheath significantly reduced total fluoroscopy time (267 ± 145 s vs. 197 ± 74 s; p=0.03), fluoroscopy dose (26.2 ± 24.7 mGy vs. 16.7 ± 16.1 mGy; p=0.04) and left atrial procedure time (72.1 ± 18.7 min vs. 61.4 ± 18.9 min; p=0.05). Total ablation time (1158 ± 347 s vs. 1067 ± 196 s; p= 0.28), number of radiofrequency pulses (78 ± 19 vs. 77 ± 32; p=0.81) and total procedure time (117.7 ± 30.0 min vs. 105.0 ± 21.4 min; 0.09) did not differ between the two groups. No major complications occurred in either group. Conclusion: Using visualizable steerable sheath for PVI procedures can reduce fluoroscopy exposure and left atrial procedure time compared to standard, non-visualizable steerable sheath in patients undergoing PVI procedures.